Insufficient gene expression and lost gene regulatory network may underlie the mechanism of Hirschsprung Disease in 5p–syndrome - Yizhao Luan; Peng Li; Yuanyuan Luo; Hong Zhang; Xiaochun Zhu; Yan Zhang; Aihua Yin; Qiang Wu; Chengwei Chai (Heliyon)
Cri-du-chat syndrome (CDC, OMIM 123450) is a rare chromosomal syndrome that results from partial deletions on the short arm of chromosome 5, known as 5p minus. Substantial clinical and genetic heterogeneity were observed in CDC patients. Large efforts have been dedicated to correlating the deleted regions on 5p arm with observed symptoms in CDC patients. However, the genetic basis of many specific phenotypes, including the co-occurrence of Hirschsprung Disease (HSCR), have yet been clarified. Here, we conducted a study on two patients with CDC and HSCR using whole genome sequencing (WGS) analyses. Our WGS data confirmed the deletion regions on 5p associated with CDC and indicated potential unknown genetic mechanisms underlying HSCR. On the one hand, leveraging human single-cell atlas for developing enteric nervous system, we demonstrated that some affected genes in these two patients overlapped with those showing expression changes along the development pseudotime of enteric nervous cells (ENC) and overlapped with known HSCR genes including RET, NRG1, ERBB (ERBB2 and ERBB3), ITGB (ITGB1). On the other hand, integrating gene regulatory relationship estimated from single cell chromatin accessibility omics of enteric neurons, we found that the 5p deletion regions contained key cis-regulatory regions for HSCR-related gene GDNF. Taken together, our study reveals the genetic basis of HSCR or intestinal phenotypes in 5p minus patients, highlighting the importance of studying gene regulatory relationships to explain phenotypic heterogeneity.